2017
DOI: 10.1155/2017/7404912
|View full text |Cite
|
Sign up to set email alerts
|

Variety of RNAs in Peripheral Blood Cells, Plasma, and Plasma Fractions

Abstract: Human peripheral blood contains RNA in cells and in extracellular membrane vesicles, microvesicles and exosomes, as well as in cell-free ribonucleoproteins. Circulating mRNAs and noncoding RNAs, being internalized, possess the ability to modulate vital processes in recipient cells. In this study, with SOLiD sequencing technology, we performed identification, classification, and quantification of RNAs from blood fractions: cells, plasma, plasma vesicles pelleted at 16,000g and 160,000g, and vesicle-depleted pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 38 publications
(53 reference statements)
1
34
0
Order By: Relevance
“…Of note, among the 14 immune-specific cell-free mRNAs selected by Ngo et al (55) as best predictors of gestational age at blood draw, 11 were also identified in our study, with CEACAM8, DEFA4, LTF, and MMP8 being among those with highest fold change. Although our results are somewhat consistent with those reported by Ngo et al (55), it should be noted that cellular and cell-free transcripts can follow different patterns in similar physiological and pathological processes (56).…”
Section: Transcriptomic Changes During Pregnancysupporting
confidence: 93%
“…Of note, among the 14 immune-specific cell-free mRNAs selected by Ngo et al (55) as best predictors of gestational age at blood draw, 11 were also identified in our study, with CEACAM8, DEFA4, LTF, and MMP8 being among those with highest fold change. Although our results are somewhat consistent with those reported by Ngo et al (55), it should be noted that cellular and cell-free transcripts can follow different patterns in similar physiological and pathological processes (56).…”
Section: Transcriptomic Changes During Pregnancysupporting
confidence: 93%
“…At the beginning of this millennium, the first extracellular sncRNAs circulating in blood were discovered [21]. Since then, a wide variety of RNA species have been found in blood plasma [22,23] and its extracellular vesicles [24] by application of high-throughput sequencing. As diagnostic and therapeutic procedures shift from biopsies towards less invasive techniques, sncRNAs circulating in the blood become of particular interest as potential blood-based biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular RNA content analysis of human biofluids and extracellular vesicles may provide insights into their biogenesis and reveal biomarkers for health and disease. There are currently four types of sequencing-based total RNA profiling of such challenging clinical samples: 1) the recent modified small RNA sequencing methods 8,9 , 2) the SOLiD total RNA sequening method 12 , 3) the Ion Proton method 13 and 4) TGIRT-sequencing using thermostable group II intron reverse transcriptases 5 . The SMARTer method assessed in our study adds a fifth promising method to the sequencing armory.…”
Section: Discussionmentioning
confidence: 99%